Exploring Teachers’ Perspectives and Strategies for Enhancing Workplace Wellbeing - Panta, Chet Nath (Journal of NELTA, 2024)
Well being is perceived as a contested, relational, interdependent, and multifaceted concept. The study explored teachers’ perceptions on well being and their efforts and organizational efforts and commitment to maintain holistic teacher well being. Underpinned by the interpretive paradigm, the study employed the PERMA model, a theory of well being and resilience. The model represents positive emotions, engagement, relationships, meaning and accomplishments to cultivate well being. Another theory employed is appreciative inquiry as a transformative approach to maintaining teacher well being. Teachers need to cultivate a sense of hope, nurturing their agency and resilience, as deficit views appear to be hurdles for maintain and flourishing well being. A sense of optimism in teachers appears to be a compass to navigate challenges and foster teacher well being. Teacher well being is a collective concern. Teachers’ awareness of cross-cutting issues of pedagogical innovations and professional sensibilities and commitments play a crucial role in maintaining their well being. Efforts and strategies adopted by teachers align with the intent of appreciative inquiry and positive psychology. The study calls for taking teacher well being as a collective commitment and an indispensable aspect to enhance team culture, thereby contributing to quality education. It requires emotional commitment and holistic understanding of the stakeholders to reduce the stress and burnout of teachers so that they can remain engaged wholeheartedly in their profession to make a difference.